Counterterrorism and Cybersecurity Total Information Awareness - Lee, Newton; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Imagine James Bond meets Sherlock Holmes: Counterterrorism and Cybersecurity is the sequel to Facebook Nation in the Total Information Awareness book series by Newton Lee. The book examines U.S. counterterrorism history, technologies, and strategies from a unique and thought-provoking approach that encompasses personal experiences, investigative journalism, historical and current events, ideas from great thought leaders, and even the make-believe of Hollywood. Demystifying Total Information Awareness, the author expounds on the U.S. intelligence community, artificial intelligence in data mining, social media and privacy, cyber attacks and prevention, causes and cures for terrorism, and longstanding issues of war and peace. The book offers practical advice for businesses, governments, and individuals to better secure the world and protect cyberspace. It quotes U.S. Navy Admiral and NATO$1 (Bs Supreme Allied Commander James Stavridis: (3z(BInstead of building walls to create security, we need to build bridges.(3y (BThe book also provides a glimpse into the future of Plan X and Generation Z, along with an ominous prediction from security advisor Marc Goodman at TEDGlobal 2012: (3z(BIf you control the code, you control the world.(3y (BCounterterrorism and Cybersecurity: Total Information Awareness will keep you up at night but at the same time give you some peace of mind knowing that (3z(Bour problems are manmade $1 (Btherefore they can be solved by man [or woman],(3y (Bas President John F. Kennedy said at the American University commencement in June 1963.s
PART I: Counterterrorism in Retrospect: Then and Now -- U.S. Intelligence Community -- PART II: Counterterrorism Technologies: Total Information Awareness and Data Mining -- The Rise and Fall of Total Information Awareness -- The Afterlife of Total Information Awareness -- Artificial Intelligence and Data Mining -- PART III: Counterterrorism Technologies: Social Media and Cybersecurity -- Social Media and Two-way Street of Total Information Awareness -- Cyber Warfare: Weapon of Mass Destruction -- Cyber Attacks, Prevention and Countermeasures -- Plan X and Generation Z -- PART IV: Counterterrorism Strategies: Causes and Cures -- Understanding Terrorism -- Cure for Terrorism -- War and Peace.
Keywords: Computer science; Data mining; Multimedia systems; Information Systems; Computer Science; Information Systems Applications (incl. Internet).; Multimedia Information Systems; Management of Computing and Information Systems; Data Mining and Knowledge Discovery